Calculation of plasma parameters of the glow discharge on the water in air at atmospheric pressure - Livia Mesarosh; Месарош Лівіа; Mészáros Lívia; Mikhailo Chuchman; Чучман Михайло; Alexander Shuaibov; Шуаібов Олександр (Scientific and Technical Translations, 2017)
Abstract. For the calculation of the electrical characteristics of plasma are used normal conditions for air and experimentally measured CVC. It allows to estimate the maximum value of the electron density for the threshold mode and breakdown.
Keywords: distilled water; plasma parameters; glow discharge